PHYTOCHEMICAL SCREENING AND ANTIPYRETIC ACTIVITY OF DILLENIA INDICA LEAVE EXTRACT ON RATS - Pooja Sharma; Abhishek Sharma; Ritesh Malvi; Surendra Kumar Jain (The Bioscan, 2026)
The present study evaluated the phytochemical composition, antioxidant activity, and antipyretic potential of the ethanolic extract of Dillenia indica leaves. The extract showed a yield of 12.5% and tested positive for major phytoconstituents, including flavonoids, phenols, tannins, proteins, and alkaloids. Quantitative analysis revealed measurable levels of total flavonoids (0.63 mg/100 mg) and phenolic content (0.47 mg/100 mg). Antioxidant activity assessed by the DPPH method demonstrated moderate free radical scavenging potential with an IC₅₀ value of 96.17 µg/mL. In the yeast-induced pyrexia model, the extract produced a dose-dependent reduction in rectal temperature, with the 350 mg/kg dose showing significant antipyretic activity when compared to the standard drug paracetamol. The findings support the traditional therapeutic use of Dillenia indica and indicate its potential as a natural antipyretic agent, warranting further investigation for bioactive compound isolation and detailed pharmacological evaluation. Keywords Dillenia indica, phytochemical screening, antioxidant activity, DPPH, antipyretic activity, yeast-induced pyrexia, flavonoids, phenols, herbal medicine